Accelerated Age-Related Degradation of the Tectorial Membrane in the Ceacam16βgal/βgal Null Mutant Mouse, a Model for Late-Onset Human Hereditary Deafness DFNB113 - Goodyear, Richard J.; Cheatham, Mary Ann; Naskar, Souvik; Zhou, Yingjie; Osgood, Richard T.; Zheng, Jing; Richardson, Guy P. (Frontiers in Molecular Neuroscience, 2019)
CEACAM16 is a non-collagenous protein of the tectorial membrane, an extracellular structure of the cochlea essential for normal hearing. Dominant and recessive mutations in CEACAM16 have been reported to cause postlingual and progressive forms of deafness in humans. In a previous study of young Ceacam16 βgal/βgal null mutant mice on a C57Bl/6J background, the incidence of spontaneous otoacoustic emissions (SOAEs) was greatly increased relative to Ceacam16+/+ and Ceacam16+/βgal mice, but auditory brain-stem responses (ABRs) and distortion product otoacoustic emissions (DPOAEs) were near normal, indicating auditory thresholds were not significantly affected. To determine if the loss of CEACAM16 leads to hearing loss at later ages in this mouse line, cochlear structure and auditory function were examined in Ceacam16+/+, Ceacam16+/βgal and Ceacam16βgal/βgal mice at 6 and 12 months of age and compared to that previously described at 1 month. Analysis of older Ceacam16βgal/βgal mice reveals a progressive loss of matrix from the core of the tectorial membrane that is more extensive in the apical, low-frequency regions of the cochlea. In Ceacam16βgal/βgal mice at 6-7 months, the DPOAE magnitude at 2f1-f2 and the incidence of SOAEs both decrease relative to young animals. By ~12 months, SOAEs and DPOAEs are not detected in Ceacam16βgal/βgal mice and ABR thresholds are increased by up to ~40 dB across frequency, despite a complement of hair cells similar to that present in Ceacam16+/+ mice. Although SOAE incidence decreases with age in Ceacam16βgal/βgal mice, it increases in ageing heterozygous Ceacam16+/βgal mice and is accompanied by a reduction in the accumulation of CEACAM16 in the tectorial membrane relative to controls. An apically-biased loss of matrix from the core of the tectorial membrane, similar to that observed in young Ceacam16βgal/βgal mice, is also seen in Ceacam16+/+ and Ceacam16+/βgal mice, and other strains of wild-type mice, but at much later ages. The loss of Ceacam16 therefore accelerates age-related degeneration of the tectorial membrane leading, as in humans with mutations in CEACAM16, to a late-onset progressive form of hearing loss.